Iowa fall report, Babs & Loren Padelford, 1984 - Padelford, Babset al; Padelford, Lorenet al (1984)
Iowa fall report, Babs & Loren Padelford, 1984, listed 68 species sighted, with some observations by Tanya Bray and Sandy Kovanda. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1984. Epson - sheet feed/flatbed